Focused ultrasound extraction (FUSE) for the rapid extraction of DNA from tissue matrices - Holmes, Hal R.; Haywood, Morgan; Hutchison, Ruby; Zhang, Qian; Edsall, Connor; Hall, Timothy L.; Baisch, David; Holliday, Jason A.; Vlaisavljevich, Eli (Methods in Ecology and Evolution, 2020)
Rapid DNA extraction is a critical barrier for routine and fieldable genetics tests for applications in conservation, such as illegal trafficking and fraudulent mislabelling. Here, we develop a non-thermal focused ultrasound extraction (FUSE) technique that creates a dense cloud of high-pressure acoustic cavitation bubbles to disintegrate targeted tissues into an acellular debris, resulting in the rapid release of entrapped DNA. In this work, we demonstrate the proof-of-concept of the FUSE technique by obtaining species identifiable sequences and shotgun sequencing reads from DNA extracted from Atlantic salmon Salmo salar tissues. Having mitigated the key risks for this technique, we hypothesize future developments with this technology can be applied to accelerate and simplify DNA extraction from exceedingly difficult samples with complex tissue matrices (i.e. fibrous tissue and timber samples) in both laboratory and field settings. Gordon and Betty Moore FoundationGordon and Betty Moore Foundation [8518]; Rhodes Trust; Schmidt Futures Foundation; Virginia Tech Department of Biomedical Engineering and Mechanics; Center for Engineering Health; Institute for Critical Technology and Applied Science; National Geographic SocietyNational Geographic Society National Geographic Society; Schmidt Science Fellows; Gordon and Betty Moore Foundation, Grant/Award Number: #8518; Rhodes Trust and Schmidt Futures Foundation; Virginia Tech Department of Biomedical Engineering and Mechanics; Institute for Critical Technology and Applied Science; Center for Engineering Health